Handbook of microbiological media - Atlas, Ronald M. , 1946- (CRC Press, 2010)
"Handbook of Microbiological Media, Fourth Edition is an invaluable reference for every medical, veterinary, diagnostic, and academic laboratory... and now in its fourth edition, it is even more complete. This edition carries on the tradition of CRC Press handbook excellence, listing the formulations, methods of preparation, and uses for more than 7000 microbiological media. With 1500 more entries than any previous edition, the handbook includes both classic and modern media used for the identification, cultivation, and maintenance of diverse bacteria, archaea, and fungi." "The breadth of culture media in this comprehensive resource is enormous and has greatly expanded in recent years with the exploration of extreme habitats and the use of molecular methods to identify new lineages of bacteria and archaea. The media also represent significant advances in the ability to use chromogenic substrates to identify specific species and strains of bacteria, e.g., E. coli O157 and methicillin-resistant Staphylococcus aureus (MRSA). These media are extremely useful for clinical diagnostics and for the protection of the food supply from pathogenic microorganisms." "The entries are arranged alphabetically by medium name and include composition, instructions for preparation, commercial sources, safety cautions, uses, and more. This reference contains the most comprehensive compilation of microbiological media available in a single volume. The only resource you need for all media types, it makes finding media for culturing diverse microorganisms quick and simple. With uniform presentations of media formulations and preparations, it presents easy-to-follow directions and cookbook recipes for preparing media. You won't find a more complete or user-friendly microbiology reference anywhere."-